2013
DOI: 10.1080/09515089.2013.815099
|View full text |Cite
|
Sign up to set email alerts
|

Causation, norms, and omissions: A study of causal judgments

Abstract: Many philosophical theories of causation are egalitarian, rejecting a distinction between causes and mere causal conditions. We sought to determine the extent to which people's causal judgments discriminate, selecting as causes counternormal events-those that violate norms of some kind-while rejecting non-violators. We found significant selectivity of this sort. Moreover, priming that encouraged more egalitarian judgments had little effect on subjects. We also found that omissions are as likely as actions to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…While it was the gardener's duty to water the plants, and he was expected to do so, the Queen of England was not responsible for the plants. Several empirical studies have confirmed the role that norms play for judgments about omissions (Clarke, Shepherd, Stigall, Waller, & Zarpentine, 2015;Henne, Pinillos, & De Brigard, 2016;Livengood & Machery, 2007). For example, when two cars collide at an intersection whereby one driver had a red light and the other one a green light, participants judge the not stepping on the brakes of the driver with the red light to be more causal (Clarke et al, 2015).…”
Section: Future Directions and Open Challengesmentioning
confidence: 94%
“…While it was the gardener's duty to water the plants, and he was expected to do so, the Queen of England was not responsible for the plants. Several empirical studies have confirmed the role that norms play for judgments about omissions (Clarke, Shepherd, Stigall, Waller, & Zarpentine, 2015;Henne, Pinillos, & De Brigard, 2016;Livengood & Machery, 2007). For example, when two cars collide at an intersection whereby one driver had a red light and the other one a green light, participants judge the not stepping on the brakes of the driver with the red light to be more causal (Clarke et al, 2015).…”
Section: Future Directions and Open Challengesmentioning
confidence: 94%
“…19 For theoretical discussions of causation by omission, see Schaffer (2000); Beebee (2004); Mellor (2004); Lewis (2004);McGrath (2005); Moore (2009); Bernstein (2014). For empirical work, see Livengood and Machery (2007); Wolff, Barbey, and Hausknecht (2010); Clarke et al (2015); Henne, Pinillos and De Brigard (2017); Bello et al (2017); Stephan et al (2017); Khemlani et al (2018); Willemsen (2019).…”
Section: Acts Versus Omissionsmentioning
confidence: 99%
“…Dependency theorists therefore have the burden of explaining how omissive causation applies to relevant agents in a particular scenario, rather than to the many other agents that might have otherwise impacted the outcome under discussion (McGrath, 2005). Following suggestions originally made by Hart and Honoré (1985), recent accounts propose that norms, typicality, and default assumptions determine the most intuitive cause of an outcome with multiple putative causes (e.g., Clarke, Shepherd, Stigall, Waller, & Zarpentine, 2013;Hall, 2007;Halpern & Hitchcock, 2014;Henne, Pinillos, & De Brigard, 2017;Menzies, 2004Menzies, , 2007.…”
Section: Omissive Causation In Philosophy and Psychologymentioning
confidence: 99%